2003
DOI: 10.1038/sj.tpj.6500189
|View full text |Cite
|
Sign up to set email alerts
|

Nine- or fewer repeat alleles in VNTR polymorphism of the dopamine transporter gene is a strong risk factor for prolonged methamphetamine psychosis

Abstract: Susceptibility to drug dependence and drug-induced psychoses is influenced not only by the pharmacological effects of the drug but also by the genetic factors of the individual. To clarify the latter, we investigated the association between methamphetamine (METH) dependence/psychosis and the hDAT1 gene (SLC6A3) encoding the dopamine transporter, which is the primary site of METH activity in the brain. Four exonic polymorphisms of the hDAT1 gene, 242C/T (exon 2), 1342A/G (exon 9), 2319G/A (3 0 UTR), and VNTR (3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
80
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(87 citation statements)
references
References 28 publications
7
80
0
Order By: Relevance
“…Some data support an association of number of repeat alleles of the DAT gene with risk for methamphetamine psychosis (Ujike et al, 2003). Further, DAT density, quantified using positron emission tomography, was decreased in methamphetamine users compared to non-users .…”
Section: Dopamine-related Genes: Amphetamine and Methamphetaminementioning
confidence: 86%
“…Some data support an association of number of repeat alleles of the DAT gene with risk for methamphetamine psychosis (Ujike et al, 2003). Further, DAT density, quantified using positron emission tomography, was decreased in methamphetamine users compared to non-users .…”
Section: Dopamine-related Genes: Amphetamine and Methamphetaminementioning
confidence: 86%
“…Thus, when the 9/9 is not combined with the 9/10 genotype, there appears to be a clear difference in stimulant response. In addition, there are also studies reporting atypical stimulant response in individuals with the 9-repeat allele in other patient groups (see Gelernter et al, 1994;Ujike et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…32,33 The median latency was 3 years. Therefore, patients were divided into two categories based on the latency of the psychotic state after the first MAP intake: less than 3 years (n ¼ 54, average ¼ 0.83 years) or more than 3 years (n ¼ 53, average ¼ 9.98 years).…”
Section: Patient Subgroupsmentioning
confidence: 99%
“…(b) Duration of psychosis after the last MAP intake: Some patients showed continued psychotic symptoms despite MAP abstinence, as reported previously. 32,33 Liability for the duration of psychosis may be determined, at least partly, by genetic variation. We previously reported that genetic variation in the dopamine transporter affects the prognosis of the psychotic state.…”
Section: Patient Subgroupsmentioning
confidence: 99%